Teori Pendekatan Tafsir: Teologis, Ideologis Ke Kritis - Zainal Arif (Institut PTIQ Jakarta, 2017)
The development of Qur’anic interpretation can be catego- rized into three periods: classical, modern and contemporary. Each of these categories of interpretation has some of the typical character- istics that we describe in detail in the following article. Each of these categories also has movements from: mythological to idiological and critical. Now, in the map of Islamic thought, these three forms of in- terpretation (classical, modern and contemporary) also have their own supportive community. The classical supporters of the classical tafsir include the salaf al-shalih and the majority of Islamic societies, later known as the scripturalist, fundamental, and traditional Isla- mists. The support community of modern interpretation is among Muslim scholars who interact with many Western scholars. The com- munity of contemporary commentators is Islamic-liberal-reformist, pluralist or substantial Islamist.